Pendekatan Simbolik Arsitektur Memorial untuk Pengalaman Emosional dan Spiritual - Bhisma Oktafian Ilhamsyah; Vijar Galax Putra Jagat Paryoko (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2026)
This study finds that symbolism in memorial architecture plays a crucial role in shaping emotional experiences and fostering collective awareness of tragedy. The Aceh Tsunami Museum case studies and the Ground Zero Memorial reveal that design elements such as form, light, materials, and spatial arrangement are employed as meaningful symbolic media. In the Aceh Tsunami Museum, formal symbolism is evident in the spiral form and the façade inspired by traditional Acehnese houses, representing an emotional journey from fear to hope and a resilient local identity. Material and spiritual symbolism emerge through water, natural light, and reflective spaces like the Prayer Well. In the Ground Zero Memorial, symbolism is expressed through voids, flowing water, and the sunken plaza landscape, signifying loss and the healing process. The findings indicate that architectural symbolism reinforces historical narratives and cultural values and creates contemplative spaces that effectively evoke empathy and spiritual awareness.